(3eLehY dWja ajg OjhGf Hf ecGfS hajg ahGFO hfhGOQ hGNHGQs - (3aNQ GdOjf Hf ecGfSs
(3ChdgG (B:s
(3GdMeO ddg GdPj ejR Ggd GdCOH HaUGMI GddSGf hLjdge Edi GdfGS HMdGhI GdefWb hGdcde GdMSGf hHYO aEf GdeQMhe GdhGdO GdJMb bhdg ef GHjGJg GdeTjOI hLhGgQg GdfUjOI s
(3BNQgG (B:s
(3bGd HYV GdSda (B: (3GdMSf GdNdb Ph bQGHI YfO GdCLGfH hGdSF GdNdb CLfHj YfO Cgdg s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3YGQa MceJ (B(127) s
Keywords: (3eJaQbGJs